Performance analysis of a cascaded dual full bridges 5, 7, and 9 levels inverter: experimental validation - Saidani, Nabil; Bachtiri, Rachid El; FRI, Abdelaziz; Hammoumi, Karima El (International Journal of Power Electronics and Drive Systems (IJPEDS), 2025)
Cascaded full-bridge inverter is a suitable topology for grid-connected applications due to its ability to generate an output voltage waveform that closely resembles a sine wave, resulting in lower total harmonic distortion (THD) factors. This article proposes the use of the selective harmonic elimination (SHE) technique to produce a 5-level voltage using a symmetrical inverter and 7 and 9-level voltage using an asymmetrical inverter composed of only two full bridges loaded by an RL circuit of 51.4 Ω and 200 mH. The study primarily focuses on analysing the impact of the number of levels on the power quality of the inverter. This includes investigating the effects of the fundamental magnitude on the produced power, as well as measuring losses in the inverter, power factor, THD factor, and fundamental magnitude for each level configuration. The study demonstrates that asymmetrical MLIs lower THD (10.9% vs. 16.7%) and increasing voltage levels enhance waveform quality but slightly reduce the fundamental voltage magnitude, impacting AC power output. The simulation analysis has been conducted using the PSIM environment, and the results have been validated through experimental measurements.